Understanding Virtual Learning Challenges: Insights from Jordanian Teachers during COVID-19 - Qandeel , Nisreen Gh.; Arouri, Yousef M. (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The study investigated the challenges faced by teachers in virtual learning environments in a developing country from their own perspectives. To achieve its objectives, a descriptive survey method was employed. A questionnaire was developed and distributed–after checking its validity and reliability—to a sample of 452 teachers selected through stratified random sampling. The findings indicated that teachers faced a moderate level of challenges overall in virtual learning environments. The results also revealed statistically significant differences in the challenges faced by teachers across all domains based on school type, with public school teachers reporting more challenges than those in private schools. However, no significant differences were found in most challenge domains based on gender, except in two specific domains: “challenges related to learners” and “challenges related to school administration,” where female teachers reported greater challenges. Additionally, no significant differences were identified across any domains of challenges based on teaching experience. The researchers recommend that the Ministry of Education create centers to evaluate virtual learning apps, expand teacher training, and enhance parental involvement in distance learning.